Feasibility study of waste ceramic powder as a filler alternative for asphalt mastics using the DSR. Issue 11 (2nd November 2021) - Rochlani, Mrinali; Canon Falla, Gustavo; Wellner, Frohmut; Wang, Dawei; Fan, Zepeng; Leischner, Sabine
Abstract : Utilisation of recycled construction and demolition waste (CDW) within pavements is a beneficial substitution technique towards sustainability. Following this approach, this research investigates the feasibility of using waste ceramic powder as an alternative filler in mastics. To evaluate the performance of the alternative ceramic filler, its physical and chemical properties were compared to a commonly used mineral filler – limestone. Mastics were made using both fillers and the same reference bitumen. These unaged and Pressure Aging Vessel (PAV) aged materials were tested using the Dynamic Shear Rheometer (DSR) to measure the rheological properties and evaluate them using the 2 Springs-2 Parabolic Elements-1 Damper (2S2P1D) model. Furthermore, fatigue and rutting resistance tests the unaged bitumen and mastics were also done using the same machine. The aging index and bitumen–filler interaction values were also calculated. The results were synthesised in a single performance diagram for visual comparison of various parameters for different materials. Overall, after comparison of various parameters, it was observed that the ceramic powder can be effectively used as a filler alternative in asphalt, having higher stiffness, better aging characteristics, higher bitumen–filler interaction and rutting resistance and similar fatigue performance to that of the limestone mastic.